(untitled) (Proceedings International Conference on Fisheries and Aquaculture, 2024)
Polillo Island is known for its beaches and marine life. However, due to destructive anthropogenic activities, residents notice a decline in natural resources. Especially evident is the decrease in fish catch. The parrotfish benefit a fisherfolk’s livelihood by contributing to daily food sources and income of the fisherfolk. With the decline in its population, local environmental officials are regulating the fishing and consumption of this species. However, stakeholder commitment is crucial in achieving any conservation goal. Understanding fisherfolk attitudes and awareness of the resource and conservation initiatives increases the success rate of policy implementation. This study aims to determine (1) the socio-demographic characteristics of the fisherfolk; (2) their awareness of policies on (a) marine species conservation and (b) the conservation status of parrotfish; (3) their attitudes towards (a) conservation initiatives and marine protection regulations, and (b) their willingness to conserve the parrotfish species. This study also seeks (4) to analyze fisherfolk’s socio-demographic characteristics’ (age, annual income, educational attainment, and fishing experience) relationship to their awareness and attitude toward parrotfish species conservation. Results were analyzed using weighted mean, Pearson R correlation, and ANOVA one-way test. To gather data, a survey was employed in three villages with a sample of 177 fisherfolk who had experienced catching parrotfish. Results show that among the socio-demographic characteristics, fisherfolk’s age and fishing experience are significantly related to their attitude toward conservation initiatives and marine protection regulations. The significance of older and experienced fisherfolk in conservation initiatives should be explored. They should be involved in encouraging new fisherfolk to conserve marine species. At the same time, conservation initiatives must be designed to benefit these experienced fisherfolk.